Dental Health Care to the Rural Population through Private Dental Institutions - Sourav Chandra Bidyasagar Bal1, Sukhvinder Singh Oberoi2, Radha Prasanna Dalai1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Republic India in the present situation is a fast developing nation whose population is more than one billiontoday. Looking at the current situation of India there is a minimal increase in the number ratio of variousdental specialized surgeons and its population. The burning issue of dentistry in India is not the insufficiencyof manpower but uniformity and equitable distribution. The most off-balanced circumstances are 68.89%people of India residing in rural areas and more than eighty-five percent dentist practicing in city areasneeds to be properly balanced. One of the issues related to the dental workforce in India is the deficientmanpower planning and projection. Due to a shortage of lawful and logical data for gauging of communitydemands and very less amount of guiding system for monitoring orofacial health care services need toguide planners. This paradoxical situation needs to be looked into immediately. At this time, public stashis scant and competed for strongly. It should not a proper time to schedule large and luxurious programs.State Governments to incorporate various suitable orofacial or oral care planning in its agenda as a matterof prime concern and create the groundwork for dental clinics at general public Hospitals, Primary HealthCenters, Sub-centers as well as at referral dental centers in rural areas, to provide oral health care to our ruralpopulation.